Drug peptide conjugates in human urine?. (January 2014) - Mitchell, Stephen; Steventon, Glyn; Waring, Rosemary
Abstract 1. Once in a while, during drug metabolism studies, an unusual or unexpected pathway is unearthed. 2. Such quirky finds open a refreshing hiatus, providing a departure from the, perhaps now mundane, textbook routes. 3. This brief missive draws attention to an interesting anecdote that may be unknown to some and concerns a substituted thioxanthenone drug.